Epigenome wide comparison of DNA methylation profile between paired umbilical cord blood and neonatal blood on Guthrie cards. Issue 5 (3rd May 2020) - Jiang, Yu; Wei, Jinfeng; Zhang, Hongmei; Ewart, Susan; Rezwan, Faisal I.; Holloway, John W.; Arshad, Hasan; Karmaus, Wilfried
ABSTRACT: DNA methylation (DNAm) in blood (umbilical cord blood and capillary blood collected after birth on Guthrie cards) during the perinatal period is being increasingly studied with the aim of identifying epigenetic markers of in utero environmental exposures or later disease development. However, the comparability in DNAm between these two sources is unknown. To this end, DNAm from the cord blood and capillary blood of 34 subjects in the Isle of Wight 3 rd Generation Birth Cohort (68 samples) were included to assess the comparability. Differences in average DNAm (overall agreement), correlations in DNAm, and intra-class correlation coefficients (ICC) in DNAm between the two sources, at each of the 430, 742 CpG sites, were evaluated. The results showed that a high proportion (70.1%) of the CpGs DNAm agreed between cord blood and neonatal blood on Guthrie cards. A small portion of CpGs showed high correlation (correlation ≥0.5) or high ICC (ICC ≥0.5) in DNAm of the whole genome. This proportion increased dramatically in differentially methylated regions (DMRs) that are associated with exposure to maternal smoking, between the two sources.